MicroRNAs in lipid metabolism and atherosclerosis. Issue 5 (October 2016) - Giral, Hector; Kratzer, Adelheid; Landmesser, Ulf
Abstract : Numerous studies have examined the role of microRNAs (miRNAs) in cell homeostasis and cardiovascular disease and have markedly improved our understanding of RNA biology in general and the potential role of miRNAs in atherosclerosis. In atherosclerosis, several miRNAs, such as miR-33a, b, miR-92a, miR-126 and others, have been identified that are relevant mediators of pathological processes, including regulation of cholesterol and lipid biosynthesis, lipoprotein metabolism and cholesterol efflux, but also immune responses, endothelial cell biology and vascular function. Further understanding of the specific roles of miRNAs in the distinct cell types involved in atherosclerosis initiation, progression and resolution may reveal new intervention strategies for the prevention and treatment of atherosclerotic cardiovascular disease.